As infrações aduaneiras à luz do direito aduaneiro internacional - Fazolo, Diogo Bianchi (2023)
This dissertation examines customs offences and penalties from a critical dogmatic perspective. It starts by defining the basic elements of Customs Law – goods, customs territory, and import/export – to provide a foundation for analyzing customs offences and their penalties. Subsequently, from the standpoint of International Customs Law, it identifies and describes how these provisions can alter and influence the domestic treatment of the subject matter. It considers it necessary, in light of this internationalization, to define customs offenses and penalties. Through the analysis of international treaties and national regulations, it highlights the visible international influence, which can contribute to the development of a punitive Customs Law, and emphasizes the need to study these international norms.